1993
DOI: 10.1111/j.1525-1446.1993.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsibilities and Reactions of Family Caregivers of Patients Dependent on Total Parenteral Nutrition at Home

Abstract: This prospective study assessed the caregiving responsibilities and reactions of family members who provide home care to a relative who is dependent on total parenteral nutrition (TPN). A short, semistructured interview based on the Roy adaptation model was used to gather data about the caregiving experiences of 20 relatives of adult TPN-dependent patients. Data were content analyzed, and frequently occurring themes identified. Results indicated that altered family responsibilities as well as negative and posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Caregiving is cognitively complex and requires the ability to maintain a demanding HPN schedule of lengthy infusions throughout the night with frequent awakenings from pump alarms and for blood glucose monitoring 56 , 57 . Caregivers of HPN and other technology‐dependent persons assemble, clean, maintain, and repair equipment 58 – 60 .…”
Section: The Role Of Family Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiving is cognitively complex and requires the ability to maintain a demanding HPN schedule of lengthy infusions throughout the night with frequent awakenings from pump alarms and for blood glucose monitoring 56 , 57 . Caregivers of HPN and other technology‐dependent persons assemble, clean, maintain, and repair equipment 58 – 60 .…”
Section: The Role Of Family Caregiversmentioning
confidence: 99%
“…Preparedness can be improved by involving family caregivers before HPN patients are discharged from the hospital and by providing caregivers with access to timely and relevant caregiving information when the patients are at home. However, in a national survey of 178 HPN families, 48% of the caregivers reported that they had not received any home care education and had not been present at hospital discharge 56 . Furthermore, family caregivers report having little access to information that guides them with their daily technology care 64 , 69 .…”
Section: The Complexity Of Caregiving Tasksmentioning
confidence: 99%
“…OLDER ADULTS RECEIVING HOME ENTERAL NUTRITION A cross-sectional design was used to study the HEN experience of older adults who depended on informal caregivers in the immediate postdischarge period, the time that Smith et al 27 described as the most challenging for families using similar home care technologies. That patients sought to prolong interviews with nutrition-related questions and requests for future visits underscores the taxing nature of this initial phase of HEN.…”
Section: March-april 2004mentioning
confidence: 99%
“…Four specific categories of challenges emerged from the data: financial, psychological, behavioral, and self-care. Congruent with other populations, caregiving was seen as financially burdensome (Aday & Wegener, 1988;Hazlett, 1989;Quint et al, 1990;Smith et al, 1993). One caregiver verbalized, "It's extremely hard.…”
Section: Challenges Of Caregivingmentioning
confidence: 99%